From H5N1 to HxNy: An epidemiologic overview of human infections with avian influenza in the Western Pacific Region, 2003-2017 - Sarah Hamid; Yuzo Arima; Erica Dueger; Frank Konings; Leila Bell; Chin-Kei Lee; Dapeng Luo; Satoko Otsu; Babatunde Olowokure; Ailan Li; WPRO Health Emergencies Programme Team (World Health Organization Regional Office for the Western Pacific, 2019)
Since the first confirmed human infection with avian influenza A(H5N1) virus was reported in Hong Kong SAR (China) in 1997, sporadic zoonotic avian influenza viruses causing human illness have been identified globally with the World Health Organization (WHO) Western Pacific Region as a hotspot. A resurgence of A(H5N1) occurred in humans and animals in November 2003. Between November 2003 and September 2017, WHO received reports of 1838 human infections with avian influenza viruses A(H5N1), A(H5N6), A(H6N1), A(H7N9), A(H9N2) and A(H10N8) in the Western Pacific Region. Most of the infections were with A(H7N9) (n = 1562, 85%) and A(H5N1) (n = 238, 13%) viruses, and most (n = 1583, 86%) were reported from December through April. In poultry and wild birds, A(H5N1) and A(H5N6) subtypes were the most widely distributed, with outbreaks reported from 10 and eight countries and areas, respectively. Regional analyses of human infections with avian influenza subtypes revealed distinct epidemiologic patterns that varied across countries, age and time. Such epidemiologic patterns may not be apparent from aggregated global summaries or country reports; regional assessment can offer additional insight that can inform risk assessment and response efforts. As infected animals and contaminated environments are the primary source of human infections, regional analyses that bring together human and animal surveillance data are an important basis for exposure and transmission risk assessment and public health action. Combining sustained event-based surveillance with enhanced collaboration between public health, veterinary (domestic and wildlife) and environmental sectors will provide a basis to inform joint risk assessment and coordinated response activities.